The Effects of a Knee Joint Injury Prevention Program on Young Female Basketball Players: A Systematic Review - Miljan Hadzovic; Predrag Ilic; Ana Lilic; Mima Stankovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
The research results referring to frequency have indicated that most of the sports injuries among athletes of both genders occur in basketball and that knee injury is the second most frequent injury during sports activities. The anterior cruciate ligament (ACL) represents one of the four most important connections for knee stability, and it is frequently prone to injury during sports activities. The aim of this paper was to determine the effects of an exercise program on the prevention of injury to the anterior cruciate ligament of the knee joint among young female basketball players. To collect existing research on the effects of the applications of prevention programs on the prevention of ACL injury in young female basketball players, the following electronic databases were searched: PubMed, SCIndeks, PEDro, J-GATE, DOAJ and Google Scholar. The analyzed studies were published between 2003 and 2018 and the participants were young female basketball players. According to the results of this study, the most frequently used training programs were neuromuscular programs, whose structure includes several types of exercises and which represented a combination of plyometric exercises, core strengthening exercises, exercises to strengthen the muscles of the lower extremities, agility exercises, flexibility exercises, and balance exercises. Finally, the application of the knee injury training program leads to an improvement in motor balance, proprioceptive abilities, balance, flexibility, as well as biomechanical abilities related to injuries of the ACL, leading to an improvement in sports performance among female basketball players.